Ionic Separation in Electrodeionization System: Mass Transfer Mechanism and Factor Affecting Separation Performance. Issue 4 (1st October 2020) - Hakim, A.N.; Khoiruddin, K.; Ariono, D.; Wenten, I.G.
Abstract : Electrodeionization (EDI), which combines the advantages of electrodialysis (ED) and conventional ion-exchange (IX) processes, has been successfully applied in the production of ultrapure water. With an ability to perform continuous and deep deionization process without regenerating chemicals, EDI has found a number of new interesting applications such as in wastewater treatment, separation and purification of biotechnology products, and other potential fields. The growing interest has necessitated the development of EDI stack construction and configuration to achieve a better performance. In addition, several studies have been performed to gain a better understanding of ion transfer mechanism in the EDI system. This paper focuses on the mechanism of ionic separation in EDI including the role of ion-exchange resin (IER) and water dissociation reaction as well as its effects on the deionization process. The main technological parameters determining EDI performance are overviewed. Membrane stack configurations along with their advantages and limitation and their development are also pointed out.